Living donor liver transplantation for hepatic malignancies in children. (2nd June 2021) - Pire, Aurore; Tambucci, Roberto; De Magnée, Catherine; Sokal, Etienne; Stephenne, Xavier; Scheers, Isabelle; Zech, Francis; Gurevich, Micheal; Brichard, Bénédicte; Reding, Raymond
Abstract: Background: Living donor liver transplantation is a treatment option for unresectable hepatic tumors in children. Methods: We enrolled 45 living donor transplantations performed between 1993 and 2018 for liver malignacies, which included hepatoblastoma ( n = 33), hepatocellular carcinoma ( n = 10), hepatic angiosarcoma ( n = 1), and rhabdomyosarcoma ( n = 1). Results: No mortality or major morbidities were encountered in any donor, and the complication rate was 9%. In the hepatoblastoma group, 5‐year overall and event‐free survival rate in recipients was 87.4% and 75.8%, respectively, and mortality was significantly higher in patients after rescue transplantation ( p = .001). Inferior vena cava replacement in these recipients appeared to be associated with reduced mortality ( p = .034), but this was not confirmed when rescue patients were excluded ( p = .629). In hepatocellular carcinoma group, both 5‐year overall and event‐free survival rates were 75.4% each, and invasion of hepatic veins was significantly associated with increased risk of recurrence and death ( p = .028). The patient with rhabdomyosarcoma died from EBV‐induced lymphoma 2 months after transplantation. The patient with angiosarcoma was in complete remission at the last follow‐up. Overall, 5‐year graft survival rate was 81.3%, and one patient underwent re‐transplantation due to chronic rejection. Conclusions: Pediatric oncological liver transplantation has become a key player in the management of malignancies with cancer cure in 84% of patients in this series. Living donor liver transplantation for pediatric recipients with unresectable tumors might be a beneficial surgical option, which is technically safe for donors and recipients, thus, allowing timely planning according to chemotherapy protocols.